Method of forming the chemical components of the professional competence of the future bachelor of laboratory diagnostics - Nikolaeva, Iryna (ScienceRise: Pedagogical Education, 2017)
The methodological foundations for formation of the chemical component of the professional competence of bachelors in laboratory diagnostics are substantiated in the article. The appropriate conditions for its formation are established, namely, the unification of the requirements for the results of training in chemistry, the study of chemical disciplines in the context of the credit-modular system of organization of the educational process in higher education institutions, the creation of a professionally oriented educational environment in the teaching of chemistry, and the systematic diagnosis of the levels of the chemical component. The essence of the stages of the forming process is determined - motivational, objective, cognitive, activity and integration. The maintenance of education of bachelors of laboratory diagnostics as a component of the developed technique by professionally oriented chemical concepts is updated. The methods for the training of chemistry (chemical equipment and reagents, natural objects, etc.), the types of training for chemical disciplines, the methods of modeling the imaginary professional situations, case studies, etc. are identified as priority for the formation of the chemical component of the professional competence of bachelors of laboratory diagnostics. (Lectures-visualizations, problem and binary lectures, practical exercises with application of group educational activity of students, active methods of training, etc.). The model of forming the chemical component of the professional competence of bachelors of laboratory diagnostics is presented. The criteria for diagnosing levels of the chemical component are given